A statistical quality control study on Malabon Soap and Oil Industrial Co., Inc. - Dichoso, Shayne Karla P.; Garrido, Kristina Q.; Rodaje, Lea Marie T.
Malabon Soap and Oil Industrial Co., Inc. has been in the oil refining industry since 1950's and continuously ranks as one of the top 1000 corporations in the Philippines. Malsoco has always pursued for high quality products and improvement of their operations. With this in mind, the company employed Statistical Quality Control Study in order to determine the factors that result to non-optimal conditions in the production system and establish measures that could help reduce the effects of these factors. Knowing the critical stages in an operation is the key to correctly plan the control scheme that should be used in the company's operations. The conduct of the study extracted the root causes of the number of problems affecting the company. High FFA content was detected as the most critical and vital root cause that results in other problems and non-optimal conditions in oil refinery. Delayed production process and refinery of nonconforming edible oil are is the main consequences associated with this problem. The study yielded some recommendations that could help the company improve its production system hence, its level of quality. Regular assessment of the equipment used in oil refining can be implemented to ensure that occasional malfunctions do not affect yield rates as well as customer feedback. Proper training of the operators and having an effective monitoring scheme is expected to contribute to the quality level of the products manufactured by Malsoco. Historical files that provide information on how to deal with various operating conditions are deemed beneficial to properly respond to failures that might occur in the system.